2011
DOI: 10.1039/c1dt10310e
|View full text |Cite
|
Sign up to set email alerts
|

Short-range correlations in d–f cyanido-bridged assemblies with XY and XY-Heisenberg anisotropy

Abstract: Two new d-f cyanido-bridged 1D assemblies [RE(pzam)(3)(H(2)O)Mo(CN)(8)]·H(2)O (RE = Sm(III), Er(III)) were synthesized and their magneto-structural properties have been studied by field-dependent magnetization and specific heat measurements at low temperatures (≥0.3 K). Below ≈ 10 K the ground state of both the Sm(III) and Er(III) ions is found to be a Kramers doublet with effective spin S = 1/2. From analyses of the low-temperature magnetic specific heat and magnetization the exchange coupling between these R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…As a matter of fact, the compounds containing Sm(III) and Gd(III) ions show a transition to 3D long-range magnetic order at TC  0.6 K and TC  0.7 K, respectively. [8][9] A similar magnetic transition is observed at TC  1 K for the Tb(III) analogue. [7] From the comparison of the (isostructural) complexes [Gd(pzam)3(H2O)M(CN)8]H2O (M = Mo and W), it appeared that the strength of the isotropic exchange interaction increases by replacing Mo(V) with W(V), probably as a result of the larger radial extent of the magnetic 5d orbitals.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…As a matter of fact, the compounds containing Sm(III) and Gd(III) ions show a transition to 3D long-range magnetic order at TC  0.6 K and TC  0.7 K, respectively. [8][9] A similar magnetic transition is observed at TC  1 K for the Tb(III) analogue. [7] From the comparison of the (isostructural) complexes [Gd(pzam)3(H2O)M(CN)8]H2O (M = Mo and W), it appeared that the strength of the isotropic exchange interaction increases by replacing Mo(V) with W(V), probably as a result of the larger radial extent of the magnetic 5d orbitals.…”
Section: Introductionsupporting
confidence: 69%
“…Previously, we reported the synthesis and magnetothermal studies of heterometallic rareearth (RE) -based cyanido-bridged 1D complexes, namely, [RE(pzam) 3 (H 2 O)Mo(CN) 8 ]·H 2 O (RE = Nd, Sm, Gd, Tb, and Er, pzam = pyrazine-2-carboxamide), whose magnetic properties are mainly determined by the particular RE ion involved. [7][8][9][10][11] We found that the Nd(III) and Mo(V) ions are coupled ferromagnetically into magnetic chains by an XY -type (planar) interaction. 10 The interaction between Tb(III) and Mo(V) is likewise ferromagnetic, but with a strong Isingtype anisotropy.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, we reported a detailed experimental study of the magnetic properties of one-dimensional d–f cyanido-bridged assemblies derived from [M(CN) 8 ] 3– and [RE(pzam) 3 ] 3+ building blocks (M = Mo(V), W(V), RE = rare earth ions, pzam = pyrazine-2-carboxamide). , In several cases, we performed the fit of the exchange interactions between neighboring metal ions and their correlation to the structure. In this paper, we report experimental and theoretical studies on the isostructural family [RE(pzam) 3 (H 2 O)W(CN) 8 ]·H 2 O (RE(III) = Gd, Tb, Dy).…”
Section: Introductionmentioning
confidence: 99%